Influência da concentração de peróxido de hidrogênio nos agentes clareadores na cor e penetração através da estrutura dental - Godoy, Monique Martins Maia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to evaluate the effects of bleaching agents on colour and the penetration of the hydrogen peroxide throughout the dental structure. One hundred cylindrical samples of enamel/dentin, obtained from bovine incisors, were prepared with 6mm of diameter and 2mm of thickness (n=20). The samples were divided into five groups, according to the concentration of hydrogen peroxide contained in bleaching gels eemployed: 20%; 25%; 30%; 35%; 40%. The samples were positioned over the artificial pulpar chambers containing an acetate buffer solution and the bleaching was performed for 30 minutes. A sample of the solution was collected and the concentration of the peroxide was measured by a spectrophotometer. To analyse the bleaching effectiveness, the chromatic coordinates Lab were measured, beforehand and one week later the bleaching procedure. The data were analysed by using the analysis of variance (ANOVA) and Tukey's test at a significance level of 5% (0.05). The mean value (+-dp) and the results of Tukey's test to hydrogen peroxide penetration were: 20%: 4.32 (±1.93) a, 25%: 4.33(±1.75) b, 30%: 6.42 (±2.64) c, 35%: 8.44 (± 3.03) d, 40%: 8.64 (±3.09) e. The results for color change were for ΔL: 20%: 2.47 (± 1.32) a, 25%: 2.55 (± 0.64)b, 30%: 2.78 (± 0.90)c, 35%: 3.30 (± 0.96)d, e 40%: 3.33 (± 1.56)e. for Δa: 20%: -0.60 (± 0.66) a, 25%: -0.71 (± 0.37) b, 30%: -0.87 (±0.42) c, 35% -0.96 (± 0.55) d, 40%: -1.09 (± 0.61) e. For Δb: 20% -3.18 (± 1.57) a, 25%: - 3.44 (± 1.17) b, 30%: -3.77 (± 1.39) c, 35%: -5.28 (± 1.42) d and 40%: -5.35 (± 1.38) e. For ΔE: 20%: -3.18 (± 1.57) a, 25%: -3.44 (± 1.17) b, 30%: -3.77 (± 1.39) c, 35%: - 5.28 (± 1.42) d, and 40% -5.35 (± 1.38) e. The groups followed by the same letter do not present significant differences. It was concluded that the increasing of peroxide concentration enhanced bleaching effect, but also increased the penetration through the tooh structure

O objetivo deste estudo foi avaliar os efeitos da concentração dos agentes clareadores na cor e penetração do peróxido de hidrogênio através da estrutura dental. Para tal foram preparadas 100 amostras cilíndricas de esmalte/dentina, com 6 mm de diâmetro e 2 mm de espessura (n = 20), obtidas a partir de dentes incisivos bovinos. Os espécimes foram divididos em cinco grupos, de acordo com a concentração de peróxido de hidrogênio contida nos géis clareadores empregados: 20%; 25%; 30%; 35% e 40%. Os espécimes foram posicionados sobre câmaras pulpares artificiais previamente preenchidas com uma solução tampão de acetato, e o clareamento foi realizado durante 30 minutos. Uma amostra de solução foi recolhida do interior da câmara pulpar artificial e a concentração de peróxido de hidrogênio mensurada em espectrofotômetro de absorbânica. Para a análise do efeito clareador, as coordenadas cromáticas L*a*b* foram mensuradas antes do procedimento e uma semana após o clareamento. Os dados foram analisados por meio de análise de variância (ANOVA) e teste de Tukey, ao nível de significância de 5%. A ANOVA mostrou diferenças significativas para penetração e cor (p<0,05). Os valores de média (±dp) e os resultados do teste de Tukey para penetração foram para cada concentração 20%:4,32 (±1,93) a, 25%: 4,33(±1,75) b, 30%: 6,42 (±2,64) c, 35%: 8,44 (± 3,03) d; 40%: 8,64 (±3,09) e. Com relação à cor, os resultados foram para ΔL: 20%: 2,47 (± 1,32) a, 25%: 2,55 (± 0,64)b, 30%: 2,78 (± 0,90)c, 35%: 3,30 (± 0,96)d, e 40%: 3,33 (± 1,56)e. Para Δa: 20%: -0,60 (± 0,66) a, 25%: -0,71 (± 0,37) b, 30%: -0,87 (±0,42) c, 35% -0,96 (± 0,55) d, e 40%: -1.09 (± 0,61) e. Para Δb: 20% -3,18 (± 1,57) a, 25%: - 3,44 (± 1,17) b, 30%: -3,77 (± 1,39) c, 35%: -5,28 (± 1,42) d e 40%: -5,35 (± 1,38) e. Para ΔE: 20%: -3,18 (± 1,57) a, 25%: -3,44 (± 1,17) b, 30%: -3,77...
Keywords: Peróxido de hidrogênio; Clareadores dentários; Cor na odontologia; Hydrogen peroxide